Hybrid scheme for glassy ion dynamics - Mohamad Sharif, Johan; Abd. Latiff, Muhammad Shafie; Ngadi, Md. Asri (2006)
Ion dynamics has largely focusing on statistical analysis of collected data from experimental or simulation results. But unfortunately, the details of the structure-transport relationships in the data have been flout in favour of ensemble average. In specifically, we deliberate a simulated 3D time-varying model of ion dynamic in glass structure and scrutinize the spatio-temporal relationship among ion dynamics. Our main aims to conceive effective representations to sustain physicist in pinpoint probability of collaborative behaviours with their spatio-temporal correlation among convoluted and seemingly messy molecule movements in ion dynamics. But it is not possible at moment. Here, we highlight the broad issues of representing ion dynamics in glassy with relation to timeline events. We put forward a hybrid scheme that used 3D glyphs for representing orientation of ion dynamic, colour scale with codeword for portray the timeline events and opacity for collaborative events. With an anthology of the schemes, we illustrated that this scheme would be able to propose an efficient tool for visually mining for whichever 3-dimensional time-varying datasets.